2019
DOI: 10.1039/c9fo00119k
|View full text |Cite
|
Sign up to set email alerts
|

Extract of ice plant (Mesembryanthemum crystallinum) ameliorates hyperglycemia and modulates the gut microbiota composition in type 2 diabetic Goto-Kakizaki rats

Abstract: Ice plant extract (IPE), a rich source of d-pinitol, has a substantial effect on ameliorating hyperglycemia and modulating gut microbiota composition in diabetic GK (Goto-Kakizaki) rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…In this study, we demonstrated that the bacterial diversity which decreased in ZDF rats was restored by LLKL treatment. In addition, we noted that Firmicutes and Bacteroidetes were the two most abundant populations in ZDF rats, which was consistent with previous studies 44,45 . Importantly, compared with the NC group, the gut microbiome in the MOD group showed a reduced abundance of Bacteroidetes and an increased proportion of Firmicutes , which resulted in an increase Firmicutes / Bacteroidetes ratio, whereas LLKL_H and LLKL_M treatments sufficiently reduced these differences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, we demonstrated that the bacterial diversity which decreased in ZDF rats was restored by LLKL treatment. In addition, we noted that Firmicutes and Bacteroidetes were the two most abundant populations in ZDF rats, which was consistent with previous studies 44,45 . Importantly, compared with the NC group, the gut microbiome in the MOD group showed a reduced abundance of Bacteroidetes and an increased proportion of Firmicutes , which resulted in an increase Firmicutes / Bacteroidetes ratio, whereas LLKL_H and LLKL_M treatments sufficiently reduced these differences.…”
Section: Discussionsupporting
confidence: 91%
“…Firmicutes and Bacteroidetes were the two most abundant populations in ZDF rats, which was consistent with previous studies. 44,45 Importantly, compared with the NC group, the gut microbiome in the MOD group showed a reduced abundance of Bacteroidetes and an increased proportion of Firmicutes, which resulted in an increase but consistent with other reports. 48,49 This evidence suggests that LLKL promotes the balance of gut microbiota in ZDF rats.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Treponema denticola and Aggregatibacter actinomycetemcomitans are increased in healthy periodontal sites in patients with insulin-dependent diabetes mellitus compared with those without diabetes mellitus (Aemaimanan et al, 2013). Decreased abundance of Treponema 2 was recorded after treatment in type 2 diabetic Goto-Kakizaki rats (Zhang et al, 2019). Campylobacter is a Gram-negative bacillus and involved in many human diseases including gastroenteritis, abortion, septicemia, inflammatory bowel disease, and periodontitis (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%